Remarkable efficiency of a pin-II proteinase inhibitor sans two conserved disulfide bonds is due to enhanced flexibility and hydrogen bond density in the reactive site loop - Joshi, Rakesh S.; Mishra, Manasi; Tamhane, Vaijayanti A.; Ghosh, Anirban; Sonavane, Uddhavesh; Suresh, C. G.; Joshi, Rajendra; Gupta, Vidya S.; Giri, Ashok P. (Journal of Biomolecular Structure & Dynamics, 2014)
Capsicum annuum (L.) expresses diverse potato type II family proteinase inhibitors comprising of inhibitory repeat domain (IRD) as basic functional unit. Most IRDs contain eight conserved cysteines forming four disulfide bonds, which are indispensible for their stability and activity. We investigated the functional significance of evolutionary variations in IRDs and their role in mediating interaction between the inhibitor and cognate proteinase. Among the 18 IRDs encoded by C. annuum, IRD-7, -9, and -12 were selected for further characterization on the basis of variation in their reactive site loop, number of conserved cysteine residues, and higher theoretical G(bind) for interaction with Helicoverpa armigera trypsin. Moreover, inhibition kinetics showed that IRD-9, despite loss of some of the disulfide bonds, was a more potent proteinase inhibitor among the three selected IRDs. Molecular dynamic simulations revealed that serine residues in the place of cysteines at seventh and eighth positions of IRD-9 resulted in an increase in the density of intramolecular hydrogen bonds and reactive site loop flexibility. Results of the serine residues chemical modification also supported this observation and provided a possible explanation for the remarkable inhibitory potential of IRD-9. Furthermore, this natural variant among IRDs showed special attributes like stability to proteolysis and synergistic inhibitory effect on other IRDs. It is likely that IRDs have coevolved selective specialization of their structure and function as a response towards specific insect proteases they encountered. Understanding the molecular mechanism of pest protease-plant proteinaceous inhibitor interaction will help in developing effective pest control strategies.An animated interactive 3D complement (I3DC) is available in Proteopedia at http://proteopedia.org/w/Journal:JBSD:39
Keywords: Capsicum annuum; Helicoverpa armigera; Proteases; Proteinase inhibitor

Repurposing the McoTI-II rigid molecular scaffold in to inhibitor of `papain superfamily' cysteine proteases - Mishra, Manasi; Singh, Vigyasa; Tellis, Meenakshi B.; Joshi, Rakesh S.; Singh, Shailja (Pharmaceuticals, 2021)
Clan C1A or `papain superfamily' cysteine proteases are key players in many important physiological processes and diseases in most living systems. Novel approaches towards the development of their inhibitors can open new avenues in translational medicine. Here, we report a novel design of a re-engineered chimera inhibitor Mco-cysteine protease inhibitor (CPI) to inhibit the activity of C1A cysteine proteases. This was accomplished by grafting the cystatin first hairpin loop conserved motif (QVVAG) onto loop 1 of the ultrastable cyclic peptide scaffold McoTI-II. The recombinantly expressed Mco-CPI protein was able to bind with micromolar affinity to papain and showed remarkable thermostability owing to the formation of multi-disulphide bonds. Using an in silico approach based on homology modelling, protein-protein docking, the calculation of the free-energy of binding, the mechanism of inhibition of Mco-CPI against representative C1A cysteine proteases (papain and cathepsin L) was validated. Furthermore, molecular dynamics simulation of the Mco-CPI-papain complex validated the interaction as stable. To conclude, in this McoTI-II analogue, the specificity had been successfully redirected towards C1A cysteine proteases while retaining the moderate affinity. The outcomes of this study pave the way for further modifications of the Mco-CPI design for realizing its full potential in therapeutics. This study also demonstrates the relevance of ultrastable peptide-based scaffolds for the development of novel inhibitors via grafting.
Keywords: Cathepsin; Clan CA cysteine proteases; cyclotide; cystatin; McoTI-II; papain; protein engineering